2020 6th International Conference on Interactive Digital Media (ICIDM) 2020
DOI: 10.1109/icidm51048.2020.9339644
|View full text |Cite
|
Sign up to set email alerts
|

Studying during Pandemic: A Review of Issues from Online Learning in the Middle of COVID-19

Abstract: Among the many sectors impacted by COVID-19 pandemic, education is one of the most affected where the existing system of students sharing spaces in physical classes is deemed too dangerous. As a response to the closure of schools and universities by the Malaysian government, Universiti Teknologi MARA was among the earliest that announced the continuation of semester via online learning. Immediately after the statement, students flocked to social medias expressing negative sentiments on the university's decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
(29 reference statements)
0
13
0
1
Order By: Relevance
“…However, after the abrupt disaster of COVID-19, a new type of apps-mediated technology emerged (Daniel, 2020;Sibert et al, 2020), specifically for live online classes in the form of blended learning (Zhao, 2020). Due to this abruptness, apps-mediated technology also brought various problems and challenges to students during online lectures (Adnan & Anwar, 2020;Ahmadon et al, 2020;Aslan, 2021;Moawad, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…However, after the abrupt disaster of COVID-19, a new type of apps-mediated technology emerged (Daniel, 2020;Sibert et al, 2020), specifically for live online classes in the form of blended learning (Zhao, 2020). Due to this abruptness, apps-mediated technology also brought various problems and challenges to students during online lectures (Adnan & Anwar, 2020;Ahmadon et al, 2020;Aslan, 2021;Moawad, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It should be noted that even though almost all students (96.5%) indicated that they had access to the internet, 3.5% mentioned they did not have access to the internet. Access to essential facilities (such as the internet) has been stressed as one of the main issues of learning during a pandemic, and its lack may be regarded as a factor promoting inequality among students [6]. Regarding whether or not they have a computer at their disposal, 91.5% of the students indicated that they had their own computer and 5.7% indicated that they had a shared computer.…”
Section: Figure 2 Student Satisfaction Regarding Instructions For Moodle and Zoommentioning
confidence: 99%
“…Studies carried out to analyse this transition point out several issues felt by teaching staff, such as poor online teaching infrastructure, lack of experience and appropriate digital skills, lack of mentoring and support [5]. Among students, issues related to technological readiness and literacy, facilities (Internet access and computer access), financial and emotional difficulties, as well as specific domestic contexts were signaled as posing more difficulties in their adaptation to online learning [6]. In the specific context of higher education institutions in Portugal, Correia and Silva [7] reported that most of the factors pointed out by students as constraints to on-line learning had to do with teachers' attitudes and skills (limited digital skills and consequently very little confidence in the use of digital tools, conservative mentality and teaching methodologies).…”
Section: Introductionmentioning
confidence: 99%
“…Pada saat pembelajaran daring mata pelajaran sejarah, otomatis tidak bisa menggunakan sarana dan prasarana yang ada di sekolah, karena adanya aturan untuk melaksanakan pembelajaran dari rumah. Sebagai pengganti sarana dan prasarana pembelajaran yang ada di sekolah, maka perlu disediakan sarana dan prasarana yang dapat diandalkan (Morgan, 2020) untuk pembelajaran daring di rumah, untuk sarana seperti handphone jenis smartphone (ponsel pintar), personal computer (PC), laptop, aplikasi belajar daring, listrik, data serta jaringan internet (Ahmadon et al, 2020;Amelia et al, 2020), sedangkan prasarana yaitu tempat belajar yang memadai di rumah masing-masing. Dari hasil survey menyatakan bahwa 99,2% siswa menyatakan bahwa pelaksanaan pembelajaran daring menggunakan handphone/smartphone, hal ini sejalan dengan penelitian yang terjadi di India bahwa hampir 80% siswa menggunakan handphone untuk mengikuti kelas online (Ahmadon et al, 2020), dan penelitian yang dilakukan oleh Agung Rachmat dan Iwan Krisnadi (2020) bahwa 97,7 % siswa SMK Negeri 8 Kota Tangerang menggunakan handphone (HP) untuk pembelajaran daring.…”
Section: Sarana Dan Prasarana Yang Dimiliki Guru Dan Siswa Untuk Pemb...unclassified